The Effect of Addiction Online Game Factor by Private High School Students in Padang City - Yolanda, Nela Sari; Marzona, Yessy; Husna, Lailatul; Azmir, Safinah (iora, 2021)
Online Game is a game that entertain which is by connected by a network, so that it can be played between one player and another player in different places. As a matter of fact, Online Game can have a negative impact, that is an addiction. Students who are addicted to play online game have been influenced by several factors, the factor of facility, individual factors, family factors, social factors, and the online game itself. An analysis that can be used to look at the factors that influence addiction online game in private senior high school students in the city of Padang is a logistic regression analysis.This type of research is experimental research and the population in this study are private senior high school students in Padang City who play online game on a smartphone. The sample in this research are about to 96 respondents and the sampling technique used was technique non probability sampling with the sampling method accidental sampling and using a questionnaire. Based on the research results, we obtained the factors that influence it and factors that significantly influence addiction online game in students private SMA is a facility, family, and types game online.